- PERANAN PEMERINTAH KOTA TANGERANG SELATAN DALAM MEMBERIKAN PERLINDUNGAN HUKUM TERHADAP FAKIR MISKIN: - - Dimas Agung Sugeng Hariyadi; Wijiningsih, Ninuk (Faculty of Law, Universitas Trisakti, 2023)
Law Number 13 of 2011 on the Handling of the destitute governs how the destitute are handled in Indonesia. The research question: does the South Tangerang City Government's responsibility in providing legal protection to the underprivileged according Law Number 13 of 2011, and what challenges does the South Tangerang City Government encounter in doing so. This research is deductive to draw conclusions from qualitatively evaluated normative legal data. According to the findings of the study and debate, the South Tangerang City Government plays a crucial role in assisting and carrying out Law Number 13 of 2011 about Handling the Poor, which establishes the legal protection of the Poor. City Social Service, in its implementation there have been many policies and programs that can help provide legal protection to the poor, there are still obstacles in its implementation. In conclusion, the TangSel City Government is related to legal protection for the poor by channeling assistance such as social cash assistance (BST) distributed directly to people who are recorded by the TangSel City Social Service, obstacles such as the lack of outreach to the community related to assistance being given, but the TangSel City Government is preparing solutions such as increasing outreach.